Răspuns :
Vo1 = 2m/s a1 = 3m/s² d1 = Vo1·Δt + a1·Δt² /2
Vo2 = 5m/s a2 = 1m/s² d2 = Vo2·Δt + a2·Δt² /2
daca cei 2 biciclisti se misca in acelasi sens : d1 = d2 + 18 d1 - d2 = 18m
(a1 - a2)·Δt² /2 + (Vo1-Vo2)·Δt - 18 = 0
2·Δt² - 6Δt - 36 = 0 Δt² - 3Δt - 18 = 0 ⇒ Δt = [3 + √(9+72)]/2 = 5,97s
d2 = 5·5,97 + 1·17,82 = 47, 67m d1 = 65,67m
Vm1 = d1/Δt1 = 65,67/5,97 = 11m/5 Vm2 = 47,67/5,97 = 7,98m/s
daca cei 2 bicicilisti se misca in sensuri opuse : d1+ d2 = 18
(a1+a2)·Δt² /2 +(Vo1 + Vo2)Δt - 18 = 0
4Δt² + 14Δt - 36 = 0 2Δt² + 7Δt - 18 = 0
Δt = [ -7 + √(49 + 144)]/4 = 1,723 s d1 = 2·1,723 +3·1,484 = 7,9 m
Vm1 = d1/Δt1 = 4,58m/5 Vm2 = d2/Δt = 6m/s
Vo2 = 5m/s a2 = 1m/s² d2 = Vo2·Δt + a2·Δt² /2
daca cei 2 biciclisti se misca in acelasi sens : d1 = d2 + 18 d1 - d2 = 18m
(a1 - a2)·Δt² /2 + (Vo1-Vo2)·Δt - 18 = 0
2·Δt² - 6Δt - 36 = 0 Δt² - 3Δt - 18 = 0 ⇒ Δt = [3 + √(9+72)]/2 = 5,97s
d2 = 5·5,97 + 1·17,82 = 47, 67m d1 = 65,67m
Vm1 = d1/Δt1 = 65,67/5,97 = 11m/5 Vm2 = 47,67/5,97 = 7,98m/s
daca cei 2 bicicilisti se misca in sensuri opuse : d1+ d2 = 18
(a1+a2)·Δt² /2 +(Vo1 + Vo2)Δt - 18 = 0
4Δt² + 14Δt - 36 = 0 2Δt² + 7Δt - 18 = 0
Δt = [ -7 + √(49 + 144)]/4 = 1,723 s d1 = 2·1,723 +3·1,484 = 7,9 m
Vm1 = d1/Δt1 = 4,58m/5 Vm2 = d2/Δt = 6m/s